Fall Risk Identification with Innovative Technologies for Aging in Place: A Clinical Needs Assessment Study - Titilola Yakubu; Nooshin Jafari; Michael Lim; Jamie Lam; Michelle Lin; Di Jiang; Kendall Ho (Canadian Geriatrics Journal, 2026)
Background Falls are a leading cause of injury and loss of independence among older adults. While gait-monitoring technologies offer promise for early fall risk detection, adoption is hindered by usability, cost, and integration challenges. Few studies incorporate perspectives from both patients and providers to inform user-centred design. Objective To identify barriers, facilitators, and design considerations for implementing gait-monitoring and fall-assessment technologies among older adults, caregivers, and healthcare providers. Methods A qualitative needs assessment was conducted with older adults (≥65 years), caregivers, and healthcare providers in British Columbia, Canada. Participants were recruited via REACH BC, community organizations, and professional networks. Data collection included demographic surveys, standardized questionnaires (EuroQol 5-Dimension 5-Level (EQ-5D-5L), Patient Activation Measure (PAM-13), Fall Efficacy Scale), and semi-structured interviews. Thematic analysis was performed using NVivo 12. Results Twenty-nine older adults/caregivers participated. Most reported slight-to-moderate functional limitations and high engagement in self-care. Four key themes emerged: (i) navigating health and fall prevention—proactive self- management but access barriers; (ii) embracing and questioning health technologies—interest tempered by complexity and perceived relevance; (iii) openness to gait monitoring and boundaries of trust—conditional acceptance, privacy concerns; (iv) designing for real lives—preferences for comfortable, discreet, affordable devices and integration into clinical workflows. Providers valued continuous data but cited cost, patient tech-readiness, and actionable output as critical. Conclusion Stakeholders expressed interest in gait-monitoring technologies that are affordable, discreet, easy to use, and respectful of autonomy. Aligning device design with both personal comfort and clinical utility, and addressing privacy and integration challenges, may improve adoption and support safe aging in place.